Measurement of the shape of the B0s→Ds∗−μ+νμ differential decay rate - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen